Rheology behaviour of low density polyethylene / clay composites - Rokiah Rahamad (Universiti Malaysia Perlis, 2008)
Low density polyethylene (LDPE) composite are prepared by incorporating clay at different loading into LDPE matrix using a Z-Blade Mixer at temperature 1800C and a rotor speed of 50 rpm for 12 minutes. A compatibilizer, polyethylene co acrylic acid (PEAA) was used to improve the compatibility of clay filled LDPE composites. The combination of LDPE and clay by composition ranging between 10, 20, 30 and 40% clay with and without compatibilizers have been investigated to study the effect of addition of clay on the flow properties of LDPE composite. The melt rheology study of LDPE/clay composites on their volumetric flow rate, shear stress, shear rate, viscosity, swelling rate and MFI value. The results show that the increasing filler loading of LDPE/clay composites has increased viscosity but reduced the volumetric flow rate, swelling rate and MFI value. The increasing of temperature indicates increase of volumetric flow and melts MFI value and decrease the viscosity and swelling rate. The presence of PEAA has increased the volumetric flow rate, viscosity, MFI value and swelling rate of LDPE/clay composites. The log viscosity of composites with and without PEAA decreases with increasing shear rate.